Removal of Methyl Orange Dye from Aqueous Solutions using Amberlite LA-2 as an Extractant - Al-abbasi, Aisha; Alammarwy , Marrow; Abdulljaoad, Safa (Journal of Pure & Applied Sciences, 2022)
The removal of methyl orange dye, MO, has been accomplished through the use of liquid-liquid extraction from aqueous solutions using Amberlite LA-2 as an extractant. UV-Vis spectroscopy was used to determine the concentration of dye in an aqueous solution. The effect of pH was studied at a specific concentration of dye and Amberlite at contact time. The effect of the initial dye concentration (20-80 ppm), and Amberlite concentration (0.011-0.044 M) on the removal rates of the dye at different contact times (15- 60 min), and temperatures of 20-40 OC have been investigated. The experimental results of extraction were used to calculate the distribution coefficient (KD), loading capacity (Z), and extraction efficiency (E%). The removal of the dye decreases with the increase in the amount of Amberlite. Moreover, there was an increase in the E % with increasing temperature. The best pH was determined to be 5.5. The maximum extraction value of about (97.65%) was obtained.